Librarian as Poet / Poet as Librarian - Erin Dorney (In the Library with the Lead Pipe, 2014)
In brief: Through interviews with three poets who also work in libraries, this article explores the benefits and challenges of these overlapping roles, reflecting on commonalities in the two communities. Introduction I am a librarian and a poet who has tried to keep those two roles separate. As a library school student and in the […]